APPLICATION OF PUBLIC SERVICE ETHICS PRINCIPLES AT GEMPOL SUB-DISTRICT OFFICE - Moch Wahid (Nindikayla Institute, 2023)
This research plan will use ethical principles in open administration at the Gempol sub-district office. The motivation behind this research is that in general, the improvement of the framework and techniques of public service administration provided by the regional apparatus must be done with careful consideration so that it is believed that it will create a good perspective of the region and the tools that offer this type of assistance. The Pasuruan Regency Government supports Bureaucratic Reform, namely towards a Clean, Accountable and Serving bureaucracy which is a value reflected in the implementation of public service administration by the apparatus at the Gempol District Office with appropriate behavior so that work can be carried out efficiently to completion